Proceedings of the 2020 4th International Seminar on Education, Management and Social Sciences (ISEMSS 2020) 2020
DOI: 10.2991/assehr.k.200826.251
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of Improper Interaction on Couriers’ Job Engagement—The Moderating Influence of Organization Support

Abstract: In the process of logistics delivery, the negative effects caused by improper interaction between customers and couriers cannot be ignored. Based on affective events theory and conservation of resources theory, this research reveals the negative conduction mechanism of improper interaction between customers and couriers from the perspective of emotional exhaustion, and verifies the moderating effect of organization support. It is found that: first, the improper interaction has significant positive effects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Table 3.1 and 3.2 present the prevalence of burnout and OS using the midpoint as cut-off. Two studies, Cheng and Chen (2020) and Wang et al (2015) did not report burnout scores and were not included in table 3.1. Three papers were not included in table 3.2 for analysis, because Apouey et al (2020) and Lian and Zhou (2019) did not report mean and SD of their results and Lin et al (2010) had a sample size (n=32) that was too small to meet the normal distribution assumption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 3.1 and 3.2 present the prevalence of burnout and OS using the midpoint as cut-off. Two studies, Cheng and Chen (2020) and Wang et al (2015) did not report burnout scores and were not included in table 3.1. Three papers were not included in table 3.2 for analysis, because Apouey et al (2020) and Lian and Zhou (2019) did not report mean and SD of their results and Lin et al (2010) had a sample size (n=32) that was too small to meet the normal distribution assumption.…”
Section: Resultsmentioning
confidence: 99%
“…Among the exacerbating factors, four studies analysed the relationship between occupational stress and burnout --one found no significant association, [19] another found 70% of the participants selected it as main factors of burnout (measured by long hours, heavy workload, safety concerns), and two found significant correlations between occupational stress and job burnout. [20,25] Other reported exacerbating factors included physical job demands, [18] customer behaviour, [17,24] low income, career prospect concerns and organizational constraints. [22].…”
Section: Main Factors Of Burnoutmentioning
confidence: 99%
See 2 more Smart Citations
“…For gig workers who are app-based and have little or no access to human managers, customer service is an important or even the single source of organizational support (Möhlmann et al, 2021). Perceived organizational support could moderate the effects of job demands on health and performance related outcomes (Cheng and Chen, 2020).…”
Section: A Jd-r Model Informed Analysismentioning
confidence: 99%